Development of a Tool to Assess Fundamental Movement Skills in Applied Settings - Platvoet, Sebastiaan; Faber, Irene R.; de Niet, Mark; Kannekens, Rianne; Pion, Johan; Elferink-Gemser, Marije T.; Visscher, Chris (Frontiers in Education, 2018)
The main aim of this study was to evaluate a new combination of test items on its practical use as a tool for determining the fundamental movement skills performance in 6- to 10-year old primary school children. This combination of tests should cover the different aspects of fundamental movement skills (i.e. locomotion, balance and object control), measure performance levels within the broad spectrum of this age range in both boys and girls and be able to detect the existing performance differences between ages. For this purpose, 1121 primary school children (6-10 years) were assessed during their regular PE class using three test items of the Korper Köordinations Test für Kinder (KTK-3), i.e. walking backwards (WB), moving sideways (MS), jumping sideways (JS), and an eye hand coordination test item (EHC). Univariate General Linear Model analyses were used to evaluate main and interaction effects of sex and age on the test outcomes. Pearson’s correlation coefficients were calculated to confirm the different constructs measured by the four test items. Moreover, in line with previous studies the raw scores were converted into movement quotients (i.e. MQKTK-3 and MQKTK-3+EHC) to classify the children’s performance level. Accordingly, percentage of agreement and Cohen’s kappa between both classifications was determined to gain insight in the influence of the addition of the EHC to the KTK-3. Significant effects for sex and age were found. Girls outperformed boys on WB and boys outperformed girls on EHC (P<0.05). On all test items children of a certain age group scored better than their 1-year younger peers, except at WB between 10- and the 8- and 9-year olds and at MS and JS between 10-year olds and 9-year olds. Moderate positive associations between the test items were found (P<0.05). An 80.8% agreement of classification of children was found based on the MQKTK-3 or the MQKTK-3+EHC (Cohen’s kappa 0.59 (P < 0.001)). Consequently, The KTK-3+EHC appears to adequately cover different aspects of the fundamental movement skills. It provides practitioners a tool that can objectively assess the broad performance spectrum within young children in applied settings, which better meets children’s individual developmental needs